Ofício, Estresse e Resiliência: desafios do Professor Universitário. - Barreto, Maria da Apresentação (2007)
The objective of this study was to investigate the elements that contribute to the state of stress which often affects those who embrace the university teaching career, and also to learn whatever strategies professors use to cope with stressing situations in order to develop resilience and a sound exercise of their profession. To the very nature of university teaching belong a variety of attributions, demands and challenges which, together, may contribute to the development of stress. The epistemological principles which guided this research were those of Complex Thinking, which facilitate a deeper comprehension of the human and social phenomena as viewed through the lens of complexity principles: the dialogical principle, the organizational recursivity principle and the hologramatical principle. Fully acknowledging the many difficulties brought about by any attempt that would try to explain human phenomena based only on one theoretical reference, we have elected multi-referentiality as the support for this study, thus being able to dialogue with a variety of authors about the same phenomenon. This was a qualitative research in which questionnaires and interviews were used as instruments for the empirical work. The data has been articulated into categories and subcategories, allowing for a thematic analysis. Participants of the study were seventeen professors from two different colleges in the city of Natal, state of Rio Grande do Norte. Bad working conditions, demands from the institution, student s lack of commitment, long working hours, low salaries, lack of incentives to university teachers, uncertainty concerning timetable and difficulties in proper time administration are the variables that contribute to the stress of professors. Although this is a problem that affects the group as a whole, strategies to cope with it are individually sought and vary from trying to find different leisure options, opening one s heart to colleagues or relatives, individual planning, prayer, rational facing of the situation, to simply giving in to exhaustion. The study has proposed institutional as well as personal actions that may foster a development among professors which takes into account a resilience development in a collective perspective. Also, it shows some articulations that are already under way so that professors may be attended to.